(untitled) (Journal of the College of Education for Women, 2019)
The Qur’an is an inexhaustible source for researchers, and all of them find a rich material for its research, and no wonder in it is the book of the greatest Arabic. Quranic research has been an attempt to extract the secret in the miracle of the Koran, and not the Quranic miracle is limited to the word and its meaning, but that the miracle extends to include every sound in motion or silent; the sound performance of the Quranic text increases the meaning of beauty and earns the word heartbeat, Souls; and this may be due to the beauty of voice in the performance and harmony between sounds and words, and harmony between the exits and descriptions, or the tides of the tides,Based on the above and to show the miraculous aspects of the Quranic statement, the idea of my research came (the aesthetic of the voice of the Quranic verse and its relation to the meaning). For everyone who reads the Book of God read in a visual sense of beauty and pleasure that is not found in the words of human beings, Whatever the secret of beautiful beauty, which is high in the Quranic text makes it a distinct text, fills the soul with certainty the greatness of God and majesty and I will try to answer through research research is based on the extrapolation of texts and analysis according to the descriptive approach.